The Arthur of the Iberians : Arthurian legends in the Spanish and Portuguese worlds - Hook, David (Arthurian literature in the Middle Ages, 2015)
This book studies the spread of Arthurian legends throughout the Spanish- and Portuguese-speaking worlds in Iberia and overseas, and the influence of those legends in literature and society there from the twelfth to the twenty-first century.